Corporate Social Responsibility in Family-Controlled Firms: A Moderated Study of Slack Resources in Indonesian Manufacturing - Haryanto, Hery; Hesniati, Hesniati; Maitri, Badra (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
The socioemotional wealth perspective emphasizes a company's concern with preserving its reputation and image. This study investigates the effects of family firms, family ownership, and family management on corporate social responsibility (CSR) disclosure, with slack resources serving as a moderating variable. Employing a quantitative approach, the analysis draws on secondary data from 118 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018-2022, yielding 590 firm-year observations. Multiple linear regression using Stata was applied. The results show that family firms have a significant negative effect on CSR disclosure, while family management has a significant positive effect. In contrast, family ownership exhibits no significant relationship with CSR disclosure. Moreover, slack resources are found to moderate the relationships between family firms, family ownership, family management, and CSR disclosure.